Catalogue of Madagascan and adjacent islands Buprestidae (Bellamy 2006): Addenda & Corrigenda - Viette, P.; Bellamy, C. L.; Aberlenc, H.-P. (Zootaxa, 2009)
Additions and corrections for the Catalogue of Madagascan and adjacent islands Buprestidae (Bellamy 2006) are given.